Potential of dendrimers as oral drug delivery carriers - P.V. Ravikanth, K.V. Ramanamurthy (Journal of Applied Pharmaceutical Science, 2018)
Macromolecules like dendrimers and their conjugates have the disadvantage of poor bioavailability due to their limited absorption from the gastrointestinal (GI) tract as a result of large molecular size and solubility characteristics. Oral bioavailability decreases substantially for molecules of molecular mass greater than 500–700 Da. Furthermore, transport by passive diffusion requires some degree of lipophilicity, unless passive absorption occurs via the paracellular route, which is generally limited to small hydrophilic molecules, i.e. 100–200 Da. Dendrimers are not exceptions to this challenge. The tight junctions that regulate paracellular transport must be altered in order to enhance the permeability of dendrimers. Tight junction modulation using fatty acids, surfactants, and alteration of lipophilicity of API are frequently used techniques for permeability enhancement. These techniques along with other techniques were discussed in detail.
Keywords: PAMAM Dendrimers,Challenges in oral delivery,Techniques to improve oral bioavailability.